Minimal state variable solutions to Markov-switching rational expectations models - Roger E. A. Farmer; Daniel F. Waggoner; Tao Zha (Federal Reserve Bank of Atlanta, 2010)
We develop a new method for deriving minimal state variable (MSV) equilibria of a general class of Markov-switching rational expectations models and a new algorithm for computing these equilibria. We compare our approach to previously known algorithms, and we demonstrate that ours is both efficient and more reliable than previous methods in the sense that it is able to find MSV equilibria that previously known algorithms cannot. Further, our algorithm can find all possible MSV equilibria in models where there are multiple MSV equilibria. This feature is essential if one is interested in using a likelihood-based approach to estimation.
Keywords: C61; C62; 330; regime switching; rational expectations; MSV; iterative algorithm; policy changes